Residential special education, market forces and integration: caught between a rock and hard place? - Robin Jackson (Scottish Journal of Residential Child Care)
The reforms implemented following the introduction of market forces, and the 'commercialisation' of care which followed the National Health Service and Community Care Act (1990), brought about far-reaching changes to the provision and financing of health and social care in the United Kingdom. Market forces received an enormous boost, 'for-profit' organisations became increasingly active, notions of 'best value' became increasingly relevant within funding formulae, and users of services were more likely to be involved in decision making (Knapp and Kavanagh, 1995). Market ideals as a key principle of public service provision continued to be an acceptable feature of the neoliberal agenda pursued by New Labour. Initially, there was the establishment of a 'quasi-market' within the public services and the 'not-for-profit' sector occupied a much more level playing field with the 'for-profit' sector. Alongside this was the increasing emphasis on integration and inclusion in education, driven by ideas such as normalisation (Wolfensberger, 1972).